2022
DOI: 10.3389/fpubh.2022.987579
|View full text |Cite
|
Sign up to set email alerts
|

Mediating role of social capital on the association between negative life events and quality of life among adults in China: A population-based study

Abstract: ObjectiveTo evaluate whether social capital played a mediating role in the relationship between negative life events (NLE) and quality of life (QoL) among adults in China after proposed a conceptual model based on stress buffering theory.MethodsA cross-sectional study was conducted based on baseline survey from the Chinese Multi-ethnic Cohort (CMEC) in Yunnan province. A total of 22,866 adults were recruited by multistage stratified cluster sampling. A structured questionnaire was used to collect the general d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Thus, this aspect still needs to be further explored in oral health promotion. Some studies have reported the role of social capital as a mediator between adverse conditions, such as low income and negative life events, and health outcomes (63). Moreover, further investigation of how social capital may interact with other factors and consequently impact oral health is also necessary.…”
Section: Future Challenges and Directionsmentioning
confidence: 99%
“…Thus, this aspect still needs to be further explored in oral health promotion. Some studies have reported the role of social capital as a mediator between adverse conditions, such as low income and negative life events, and health outcomes (63). Moreover, further investigation of how social capital may interact with other factors and consequently impact oral health is also necessary.…”
Section: Future Challenges and Directionsmentioning
confidence: 99%